Metacrinology - Sanjay Kalra; Sambit Das; Shehla Shaikh; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
This meta-thinking communication explores the concept of metacrinology through various prisms. The Greek prefix ‘meta’ has place of pride in metabolism, metamorphosis, metastasis, and meta-analysis. We now suggest its use as part of metacrinology, to convey the ever-expanding vastness of hormonal anatomy and function, as well as homeostasis and ill-health. Metacrinology can be defined in various ways. The most comprehensive definitions, however, are the study of endocrinology, beyond currently accepted pathways, paradigms, and processes, in an openminded, evidence-based manner, so as to explore and elucidate newer physical and functional facets of hormonal health and disease. Keywords: Endocrinology, metabolism, metaverse.